Transaction costs and investment in irrigation pumps: Evidence from Nigeria - Takeshima, Hiroyuki; Adeoti, Adetola I.; Salau, Sheu (International Food Policy Research Institute, 2009)
Small-scale private irrigation schemes (SPRI) have been the major driving force behind the expansion of irrigated areas in Nigeria, despite government efforts to promote large scale public irrigation schemes. SPRI allows adjustment of irrigation schedules in accordance with observed crop needs. The irrigated area in Nigeria is, however, far below its potential and an increase in farmers’ investment in irrigation is essential. While Nigerian farmers’ low level of investment in irrigation may be partly due to low returns, it is also the result of high transaction costs associated specifically with making such an investment. Although reducing transaction costs is important because the reduction provides farmers with a more enabling environment, transaction costs are often unobservable and little is known about what factors contribute to them. This brief provides insights into how farmers’ socioeconomic characteristics relate to the transaction costs in irrigation pump investment. It also offers policy options to reduce such costs.